Reformulation of the Authority of the Deposit Insurance Corporation Within the Framework of the P2sk Law - Diana Napitupulu; Inri januar (Jurnal Hukum, 2026)
The reform of the financial sector governance framework in Indonesia through Law Number 4 of 2023 concerning Financial Sector Development and Strengthening (P2SK Law) and its subsequent amendment has significantly transformed the institutional role of the Deposit Insurance Corporation (LPS). This study examines the legal implications of strengthening LPS authority in maintaining financial system stability, focusing on legal certainty, institutional accountability, and regulatory balance. Using a normative (doctrinal) legal research method, this study applies statutory, conceptual, and comparative approaches to analyze relevant legal frameworks, including the LPS Law, P2SK Law, and subsequent regulatory developments. The findings indicate that the post-P2SK framework has expanded LPS functions beyond deposit protection and bank liquidation toward a more comprehensive financial safety net mechanism involving prevention, resolution planning, and systemic risk management. However, the expansion of authority also creates challenges related to institutional coordination, moral hazard, and accountability mechanisms. The study argues that strengthening LPS requires not only broader legal authority but also clear governance safeguards, transparency, and harmonized relationships with other financial authorities, particularly Bank Indonesia and the Financial Services Authority. The reform of LPS represents an important advancement in Indonesia’s financial stability architecture, provided that institutional power is balanced with effective legal control mechanisms.